2012
DOI: 10.1073/pnas.1205867109
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cells sequester antigenic epitopes for prolonged periods in the absence of antigen-encoding genetic information

Abstract: Studies with a number of viral systems have shown, on the basis of the ability of a host to prime naïve T cells, that viral antigens persist in the infected host well beyond complete clearance of the infection and even when viral antigen is undetectable by the most sensitive methods. This has led to a reasonable assumption that the antigen persists through persistence of antigen-encoding genetic information (DNA or RNA) that resides in the host at a subdetectable level. Here, we demonstrate that epitopes, or e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…During acute infections, microorganisms may replicate for weeks, thus providing continuous supply of antigen that may enter and sustain germinal center reactions. Soluble protein from subunit vaccines can be detected in the draining LNs already a few hours post immunization and is cleared much more rapidly, with intact antigen being non-detectable at 24-72 h later (11,37). Mature naïve B cells are not found in muscle tissue, a common site for vaccine injection, but are circulating between follicles of secondary lymphoid organs.…”
Section: Discussionmentioning
confidence: 99%
“…During acute infections, microorganisms may replicate for weeks, thus providing continuous supply of antigen that may enter and sustain germinal center reactions. Soluble protein from subunit vaccines can be detected in the draining LNs already a few hours post immunization and is cleared much more rapidly, with intact antigen being non-detectable at 24-72 h later (11,37). Mature naïve B cells are not found in muscle tissue, a common site for vaccine injection, but are circulating between follicles of secondary lymphoid organs.…”
Section: Discussionmentioning
confidence: 99%
“…This concerted processing event and timed-translocation could explain how gp96-chaperoned peptides are presented on MHC I or MHC II by the same APC. We also observed the persistence of peptide within the cytosol of cells which could be the result of re-association of peptide with endogenous HSPs within the APC (38,49,51,53,54). …”
Section: Discussionmentioning
confidence: 77%
“…The immature DC phenotype of the P6 sub-population, with a higher capacity for antigen uptake, and possibly a higher antigen sequestering capacity, may be responsible for this superior activity. Luketic et al [ 35 ] and Li et al [ 36 ] have previously demonstrated that DCs have a unique ability to sequester antigenic epitopes or their precursors for extended periods of time, up to several weeks. Here, we speculate that the P6 sub-population has a better antigenic sequestering ability than the P5.…”
Section: Discussionmentioning
confidence: 99%
“…Using two distinct methods of analysis, our results show clearly that DCs act in both capacities, although un-equally. The major contribution towards the adjuvanticity of DCs derives from their role as ADCs, possibly because of the unusual capacity of DCs to sequester antigen for prolonged periods of time [ 36 ]. The identification of a specific sub-set of DCs with the highest adjuvanticity as well as a better understanding of the mechanisms of their adjuvanticity lays a foundation for further investigations and comparison of CD11c + MCHII lo cell sub-population to a possible human DC counterpart in order to use DCs as highly effective adjuvants in neoepitope-based cancer vaccines.…”
Section: Discussionmentioning
confidence: 99%